2011
DOI: 10.1029/2010ja016367
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceleration by an Alfvénic pulse propagating in an auroral plasma cavity

Abstract: [1] With the help of a 2.5-D particle-in-cell simulation code, we investigate the physics of the acceleration of auroral electrons, through the interaction of an isolated Alfvén wave packet with a plasma density cavity. The cavity is edged by density gradients perpendicular to the magnetic field. We show that a single passing of an isolated wave packet over a (infinite) cavity creates an electron beam. It triggers local current and beam-plasma instabilities and small-scale coherent electric structures. The ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…We can see high frequency oscillations that do not propagate; they are simply a noise background oscillating around the plasma frequency (ω = 1). As in Mottez and Génot (2011), this noise is enhanced at the initial position of the wave packets because of an imperfect initialization of the Alfvén wave modes. More interesting, we can see that around time 200, when the two wave packets strongly interact, there is the emergence of an electric structure that does not propagate and that lasts as long as the two wave packets cross each other.…”
Section: F Mottez: Parallel Electric Fieldsmentioning
confidence: 87%
See 1 more Smart Citation
“…We can see high frequency oscillations that do not propagate; they are simply a noise background oscillating around the plasma frequency (ω = 1). As in Mottez and Génot (2011), this noise is enhanced at the initial position of the wave packets because of an imperfect initialization of the Alfvén wave modes. More interesting, we can see that around time 200, when the two wave packets strongly interact, there is the emergence of an electric structure that does not propagate and that lasts as long as the two wave packets cross each other.…”
Section: F Mottez: Parallel Electric Fieldsmentioning
confidence: 87%
“…This way of initializing Alfvén wave packets has already been applied and tested by Mottez and Génot (2011). It was shown that for a single wave packet propagating on a uniform plasma, the packet is not destroyed by the dispersion.…”
Section: F Mottez: Parallel Electric Fieldsmentioning
confidence: 99%
“…Thus, the accelerated population represents some beams in energy space. The relaxation of this kind of beam in inhomogeneous plasma results in the generation of low-frequency electrostatic waves (Mottez & Génot 2011). As a result, electron acceleration by KAWs may increase a level of electrostatic turbulence, which effectively scatters electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Mottez and Génot [8] studies the interaction of an isolated Alfven wave packet with a plasma density cavity. Tsiklauri [7] considered particle acceleration by DAWs in the transversely inhomogeneous plasma via full kinetic simulation particularly focusing on the effect of polarization of the waves and different regimes (inertial and kinetic).…”
Section: Introductionmentioning
confidence: 99%
“…As described in Tsiklauri [7,12], presence and damping of magnetohydrodynamic (MHD) waves is of importance to several problems: (i) The solar coronal heating problem [13], (ii) Earth magnetosphere energization in the context of electron acceleration by Alfven harmonic waves and pulses propagating in an auroral plasma cavities [8,[14][15][16]. (iii) Fast acceleration of inner magnetospheric hydrogen and oxygen ions by shock induced ULF waves [17].…”
Section: Introductionmentioning
confidence: 99%